SCHOOL OF MANCHESTER: THE FUTURE IS IN THE PAST - Emilia UNGUREANU; Felix-Constantin BURCEA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2015)
In a period full of uncertainties, economists belonging to different economic schools are trying to find solutions for overcoming recession moments and for ensuring a sustainable economic growth. A phenomenon usually found in physics, hysteresis, is according to our opinion, applicable in both theory and economic practice: the current economic situation, but also governing theories and laws, are influenced and dependent of past events. We will turn our attention in this article on Manchester Economic School, a less orthodox one, but with strong principles that are still influencing the contemporary realities.